2022
DOI: 10.1038/s41401-021-00835-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of colchicine in cardiovascular medicine: a pharmacological review

Abstract: Colchicine is an ancient herbal drug derived from Colchicum autumnale . It was first used to treat familial Mediterranean fever and gout. Based on its unique efficacy as an anti-inflammatory agent, colchicine has been used in the therapy of cardiovascular diseases including coronary artery disease, atherosclerosis, recurrent pericarditis, vascular restenosis, heart failure, and myocardial infarction. More recently, colchicine has also shown therapeutic efficacy in alleviating cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 312 publications
(192 reference statements)
1
55
0
4
Order By: Relevance
“…At low doses, colchicine prevents growth of microtubules, while it supports microtubule depolymerization at high doses. Colchicine’s effect on tubulin disruption prevents the formation of the inflammasome which results in less secretion of pro-inflammatory cytokines and impaired neutrophil function ( 9 , 19 ). Given this background, colchicine was explored as a novel anti-inflammatory treatment strategy in patients with coronary artery disease (CAD).…”
Section: Discussionmentioning
confidence: 99%
“…At low doses, colchicine prevents growth of microtubules, while it supports microtubule depolymerization at high doses. Colchicine’s effect on tubulin disruption prevents the formation of the inflammasome which results in less secretion of pro-inflammatory cytokines and impaired neutrophil function ( 9 , 19 ). Given this background, colchicine was explored as a novel anti-inflammatory treatment strategy in patients with coronary artery disease (CAD).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Deftereos et al performed a randomized clinical trial of patients with coronavirus infection and observed that participants who received colchicine had significantly improved time to clinical deterioration with HD (48). These recent study reported the benefit of colchicine in the prevention of coronavirus-related heart injury (11,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine, another anti-inflammatory drug, showed beneficial effects on cardiovascular outcomes in patients with stable ( Nidorf et al, 2020 ) and acute coronary disease ( Tardif et al, 2019 ). Colchicine, at the molecular level, inhibits NLRP3 inflammasome, in addition to the inhibition of nuclear factor kappa B ( Zhang et al, 2022 ).…”
Section: Inflammation and Recurrent Ischemic Eventsmentioning
confidence: 99%